Exploitation of cavitation-enhanced heating for release of doxorubicin from thermosensitve liposomes by therapeutic ultrasound. - Mylonopoulou, E; Bazan-Peregrino, M; Arvanitis, C; Coussios, C (2010)
The systemic toxicity of current chemotherapeutic treatments motivates the investigation of targeted delivery techniques to restrict the action of drugs to the tumor region. ThermoDox(©) copyright (Celsion Corporation) consists of doxorubicin, a common anticancer agent, encapsulated within thermally sensitive liposomes designed to release their contents above 39 °C. Activation of such an agent with the use of HIFU, which can generate localized heating non-invasively, potentially combines the benefits of targeted chemotherapy and hyperthermia while minimizing undesirable systemic side-effects. ThermoDox(©) release was investigated and optimized in a novel cell-embedding, tissue-mimicking material. The material was exposed to 1.1 MHz HIFU using a range of clinically relevant pressure amplitudes, duty cycles, and exposure durations to identify optimal insonation conditions for complete doxorubicin release, resulting in cell death that is solely due to drug activity. The corresponding temperature profiles were mapped throughout the focal region using embedded needle thermocouples. Drug release and cell viability were quantified using fluorescent microscopy and cell luminescence, respectively. Optimal conditions for drug release only due to the thermal effects of HIFU, with and without cavitation, were identified and cell death only due to drug release was achieved, demonstrating the potential for safe and effective targeted drug release by HIFU-induced hyperthermia.